PELATIHAN PENINGKATAN KOMPETENSI SUPERVISI KEPALA SEKOLAH DAN GURU PAMONG DALAM PENDAMPINGAN PPL MAHASISWA PGSD FKIP UNIVERSITAS MATARAM DI GUGUS 2 KOTA MATARAM - Moh. Irawan Zain; Sudirman Sudirman; Abdul Kadir Jaelani (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2021)
The purpose of this activity is to provide supervision provisions for school principals and tutors so that tutors in particular are able to provide correct and measurable assistance to PGSD FKIP students who carry out PPL in elementary schools. The problem in this service is the lack of maximum assistance carried out by civil servant teachers to PPL students in Mataram District. The method applied in this counseling is multi-method, namely the lecture method, question and answer method, and demonstration method as well as the assignment method. The training was held at SDN 19 Mataram with a total of 34 teachers. It should be stated that this service was quite successful because 80% of all participants who were targeted for the training managed to complete the given training tasks. The number of participants who took part in the training was 34 of the 30 people planned, this result was due to the request of the principal from cluster 2 of Mataram District on average asking for additional participants, this means that the implementation of this service has met the previously desired standards.